Volodymyr Zelensky: What has Been Done in the Past Year? What’s Next? - Donaj, Łukasz (Wydawnictwo Naukowe Wydziału Nauk Politycznych i Dziennikarstwa UAM, 2020)
The paper sets out to assess the first year of Volodymyr Zelensky’s presidency. By analyzing the decision-making process followed by Zelensky (using the decision-making, institutional-legal, systems, induction and deduction methods), the author attempts to answer whether the process serves Ukraine and its long-term interests. By identifying the determinants affecting Ukraine’s foreign policy, the author tries to show the long term prospects for the country.

Treścią publikacji jest próba oceny pierwszego roku prezydentury W. Zełenskiego. Dokonując analizy procesu podejmowania decyzji przez W. Zełenskiego (posiłkując się metodą decyzyjną, instytucjonalno-prawną, systemową oraz indukcją i dedukcją) autor próbował odpowiedzieć, czy jest to działanie służące Ukrainie i jej dalekosiężnym interesom. Określając determinanty wpływające na politykę zagraniczną Ukrainy, autor starał się ukazać, co w dalszej perspektywie czeka kraj nad Dnieprem.
Wołodymyr Zelenski: Co zrobiono w minionym roku? Co dalej?...
Keywords: Ukraine; European Union; Revolution of Dignity; presidency; prospects for European integration; Ukraina; Unia Europejska; rewolucja godności; prezydentura; perspektywy integracji europejskiej